Information competencies in the initial teacher training of a peruvian university - Turpo-Gebera, Osbaldo; Pérez-Postigo, Gerber; Diaz-Zavala, Rocío; Venegas-Mejía, Valia; Esquivel Grados, José (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Information management is a substantial activity in initial teacher training and for coexistence in the digital society. Hence the need to diagnose the informational competencies of teachers in training, in order to determine their shortcomings and expectations of achievement. For this purpose, the IL-HUMASS (Information Literacy Humanities Social Sciences Survey) questionnaire was applied to 344 students of nine pedagogical specialties of a faculty of education. The results show the differences in acquisition, in terms of the importance and self-efficacy attributed to informational competencies, and the need to redesign teacher training.